A simple approach for fabrication of interconnected graphitized macroporous carbon foam with uniform mesopore walls by using hydrothermal method. (June 2015) - Karthik, M.; Faik, A.; Doppiu, S.; Roddatis, V.; D'Aguanno, B.
Abstract: Three-dimensional (3D) highly interconnected graphitized macroporous carbon foam with uniform mesopore walls has been successfully fabricated by a simple and efficient hydrothermal approach using resorcinol and formaldehyde as carbon precursors. The commercially available cheap polyurethane (PU) foam and Pluronic F127 were used as a sacrificial polymer and mesoporous structure-directing templates, respectively. The graphitic structure of carbon foam was obtained by catalytic graphitization method using iron as catalyst. Three different carbon foams such as graphitized macro-mesoporous carbon (GMMC) foam, amorphous macro-mesoporous carbon (AMMC) foam and graphitized macroporous carbon (GMC) foam were fabricated and their physicochemical and mechanical properties were systematically measured and compared. It was found that GMMC possess well interconnected macroporous structure with uniform mesopores located in the macroporous skeletal walls of continuous framework. Besides, GMMC foam possesses a well-defined graphitic framework with high surface area (445 m 2 /g), high pore volume (0.35 cm 3 /g), uniform mesopores (3.87 nm), high open porosity (90%), low density (0.30 g/cm 3 ) with good mechanical strength (1.25 MPa) and high electrical conductivity (11 S/cm) which makes it a promising material for many potential applications.